2011
DOI: 10.3758/s13420-011-0051-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the amount of acquisition and contextual generalization on the renewal of instrumental behavior after extinction

Abstract: Four experiments with rat subjects examined the role of context during the extinction of instrumental (freeoperant) behavior. In all experiments, leverpressing was first reinforced on a variable-interval 30-s schedule and then extinguished before being tested in the extinction and renewal contexts. The results identified three important variables affecting the renewal effect after instrumental extinction. First, ABA and ABC forms of renewal were strengthened by increasing the amount of acquisition training. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
92
0
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 97 publications
(104 citation statements)
references
References 25 publications
(35 reference statements)
9
92
0
1
Order By: Relevance
“…The low number of responses during extinction is striking, when compared with those from the second training day in both experiments, a finding that highlighted the importance of the reinforcer in maintaining this response. In adult rats, the magnitude of operant responding with appetitive reinforcers is likewise markedly reduced during extinction, compared to responses during an acquisition phase (e.g., Bouton et al, 2011;Todd et al, 2012b), suggesting that this outcome may be a pattern inherent to certain types of procedures involving appetitive operant conditioning, not necessarily related to the young age of the subjects in the present study.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…The low number of responses during extinction is striking, when compared with those from the second training day in both experiments, a finding that highlighted the importance of the reinforcer in maintaining this response. In adult rats, the magnitude of operant responding with appetitive reinforcers is likewise markedly reduced during extinction, compared to responses during an acquisition phase (e.g., Bouton et al, 2011;Todd et al, 2012b), suggesting that this outcome may be a pattern inherent to certain types of procedures involving appetitive operant conditioning, not necessarily related to the young age of the subjects in the present study.…”
Section: Discussionmentioning
confidence: 69%
“…Bouton and colleagues have reported renewal by using operant conditioning settings, and showed that context can affect similarly the extinction of a pavlovian or an operant response (e.g., Bouton et al, 2011;Todd, Winterbauer, & Bouton, 2012a, 2012b. To date, no studies have addressed in infant rats the possibility of renewal of an extinguished operant response.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, in a renewal preparation, Todd, Winterbauer, and Bouton (2012) arranged an ABC renewal paradigm where responding was initially established in Context A with one set of global environmental features (e.g., scent, textures, visual patterns). They extinguished responding in a second and novel Context B.…”
Section: Discussionmentioning
confidence: 99%
“…For example, operant renewal is a relapse phenomenon that occurs when contextual stimuli present during the extinction of an operant response are changed. In animal studies of renewal, contextual stimuli can consist of a flashing versus steady operant chamber illumination (Podlesnik& Shahan, 2009), a distinctive scent (e.g., Bouton et al, 2011), stripes on the side of the operant chamber (e.g., Todd et al, 2012), and/or a combination of multiple such olfactory and visual stimuli (Bouton et al, 2011; Todd et al, 2012). For example, a rat might be trained to press a lever to receive a food pellet in one context (context A), but moved to a novel context (B) where no food is available for the target response (i.e., extinction).…”
Section: Introductionmentioning
confidence: 99%